Posaconazole-hemp seed oil loaded nanomicelles for invasive fungal disease - Anjali Rathee; Pavitra Solanki; Nasr A. Emad; Iqra Zai; Saeem Ahmad; Shadab Alam; Ali S. Alqahtani; Omar M. Noman; Kanchan Kohli; Yasmin Sultana (Scientific Reports, 2024)
Abstract Invasive fungal infections (IFI) pose a significant health burden, leading to high morbidity, mortality, and treatment costs. This study aims to develop and characterize nanomicelles for the codelivery of posaconazole and hemp seed oil for IFI via the oral route. The nanomicelles were prepared using a nanoprecipitation method and optimized through the Box Behnken design. The optimized nanomicelles resulted in satisfactory results for zeta potential, size, PDI, entrapment efficiency, TEM, and stability studies. FTIR and DSC results confirm the compatibility and amorphous state of the prepared nanomicelles. Confocal laser scanning microscopy showed that the optimized nanomicelles penetrated the tissue more deeply (44.9µm) than the suspension (25µm). The drug-loaded nanomicelles exhibited sustained cumulative drug release of 95.48 ± 3.27% for 24 h. The nanomicelles showed significant inhibition against Aspergillus niger and Candida albicans (22.4 ± 0.21 and 32.2 ± 0.46 mm, respectively). The pharmacokinetic study on Wistar rats exhibited a 1.8-fold increase in relative bioavailability for the nanomicelles compared to the suspension. These results confirm their therapeutic efficacy and lay the groundwork for future research and clinical applications, providing a promising synergistic antifungal nanomicelles approach for treating IFIs.